2018
DOI: 10.1021/acs.jpcc.8b02071
|View full text |Cite
|
Sign up to set email alerts
|

Explicit Flue Gas Adsorption Isotherm Model for Zeolite 13X Incorporating Enhancement of Nitrogen Loading by Adsorbed Carbon Dioxide and Multi-Site Affinity Shielding of Coadsorbate Dependent upon Water Vapor Content

Abstract: Carbon capture from flue gas by adsorption processes requires a suitable isotherm model for use in process simulators. Comparative physical adsorption isotherm models are here tested on an adsorption equilibrium loading data set for Zeolite 13X (Z13X) between 298 and 348 K. Dry flue gas mixture adsorption was found to involve enhanced adsorption of N 2 by up to 85% relative to levels of N 2 mixture adsorption predicted with pure species parameters. This relative N 2 deviation was found strongly dependent upon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…298 Simulation results from Purdue and Qiao illustrated that adsorption of water in zeolite 13X removed water molecules in site II of the FAU framework and that CO 2 molecules moved towards the SOD cage. 278,299 The authors examined the impact of RH on the capture of CO 2 from flue gas with 20% CO 2 at 25 1C and found that CO 2 adsorption remained in site III for RH below 15% before a complete exclusion by H 2 O in higher RH. The unique behavior in the site III could be due to the formation of chemisorbed carbonates as the cations in this position are electrostatically less-shielded.…”
Section: Competitive Adsorption Between Co 2 and H 2 Omentioning
confidence: 99%
“…298 Simulation results from Purdue and Qiao illustrated that adsorption of water in zeolite 13X removed water molecules in site II of the FAU framework and that CO 2 molecules moved towards the SOD cage. 278,299 The authors examined the impact of RH on the capture of CO 2 from flue gas with 20% CO 2 at 25 1C and found that CO 2 adsorption remained in site III for RH below 15% before a complete exclusion by H 2 O in higher RH. The unique behavior in the site III could be due to the formation of chemisorbed carbonates as the cations in this position are electrostatically less-shielded.…”
Section: Competitive Adsorption Between Co 2 and H 2 Omentioning
confidence: 99%
“…In unraveling these global assignments, immense interest has been provoked on porous materials, setting a new paradigm in material science. Porous materials such as metal–organic frameworks (MOFs), covalent organic framework (COF), and zeolites are well-studied systems for their guest uptake properties. MOF and COFs have a remarkable advantage over zeolites due to their pore size specificity, and tailor-made frameworks for targeted specific nature. Both MOF and COF have a plethora of applications in energy storage, gas separation, catalysis, and electronics. In spite of the early success of these polymeric materials in the sequestration of toxic gases, their rigid nature in the presence of open metal sites limits their robust use.…”
Section: Introductionmentioning
confidence: 99%